The relevance of citizen involvement in Health Technology Assessment. A concrete application in the assessment of HPV co-testing in the Autonomous Province of Trento (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundSpecific programs have been developed in the latest decades to involve patients in Health Technology Assessments (HTAs). However, there are no structured practises in Italy and citizen’ perspective is rarely included in HTA reports. Aim of this study is to explore citizen’ opinions about cervical cancer screening with Human Papillomavirus (HPV) co-testing in the Autonomous Province of Trento (PAT).MethodsTwo focus groups were conducted: one with representatives of patients’ associations, the other one with women between 31 and 64 years and their family members. Following aspects were investigated: the importance of cervical cancer screening programs; the impact of HPV test on women’ and their partners’ life; needs, expectations, and critical aspects of the new screening method.ResultsOrganised screening programs are very important for all participants. HPV co-testing screening is preferred to cytology for its higher sensitivity, but different opinions came out regarding the longer screening interval after normal HPV and Pap test results. Citizen stressed that correct, clear, and unambiguous information have to be provided to the whole population (men included). A cardinal role plays the patient-doctor relationship in informing and taking care, also emotionally, of women, their partners and relatives in case of positive HPV test.ConclusionIn order to facilitate the introduction of the new screening method, various media must be used to spread clear and unambiguous information, as well as informative and educational meetings with doctors and caregivers. Citizen perspective was included in the report for the Health Trust and played an important role in the decision process.